Clinico-physiological profile of patients of pulmonary impairment after tuberculosis at a tertiary care centre - Singh, Gajendra V.; Srivastava, Antriksh; Chandra, Vinisha; Kumar, Santosh; Goel, Rishabh (International Journal of Research in Medical Sciences, 2018)
Background: Pulmonary tuberculosis (TB) is a unique infectious disease that more often results in permanent structural changes in the lung parenchyma. It is by virtue of these changes that the patients even after bacteriological cure continue to suffer the after effects of the disease. Objective of study was to assess the clinico-physiological profile of patients of pulmonary impairment after tuberculosis (PIAT) attending S. N. Medical College, Agra, Uttar Pradesh, India. Methods: Over the time period of 2 years, 350 patients of healed pulmonary tuberculosis were identified and studied about their clinico-physiological profile. This profile included age, sex, category of treatment, pulmonary function test pattern, exercising capacity, exercise tolerance and quality of life. Results: It was found that majority of the patients were males, >60 years of age and had taken Category-II treatment. Most of the patients were having an obstructive pattern on PFT, poor exercise tolerance and exercise capacity and a poor quality of life. Conclusions: Patients of healed pulmonary TB continue to experience respiratory symptoms owing to the permanent anatomical changes in the lung conferred by the disease.